ANALISIS IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PENDIDIKAN KEWARGANEGARAAN DI KELAS 5 SEKOLAH DASAR KARDULUK IV - Ruski, Moh. Syamil; Shiddiq , Ahmad Shiddiq; Ridwan , M Ridwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Civic Education (PKn) serves as the primary means of instilling Pancasila values from an early age. This study aims to analyze the implementation of Pancasila values in PKn lessons in grade 5 at SD Karduluk IV. The questions addressed include students’ understanding and attitudes towards Pancasila values, the methods teachers use to instill these values, the role of the school environment in supporting the implementation of Pancasila, the challenges faced in implementing Pancasila values, and the efforts made by the school to overcome these challenges. The research method used is a qualitative approach with a descriptive method. The results show that teachers apply various teaching methods such as group discussions, simulations, and case studies to instill Pancasila values in students. However, there are still some challenges in its implementation, such as students’ lack of understanding of the concepts of democracy and justice, as well as limited interactive learning media. Therefore, innovation in teaching methods and the use of technology are needed to improve the effectiveness of teaching Pancasila values. This study is expected to provide insights for schools in improving the quality of PKn education based on Pancasila values.